2007
DOI: 10.1111/j.1440-1681.2007.04594.x
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone, an Agonist of Peroxisome Proliferator‐activated Receptor‐gamma, Prevents Contralateral Testicular Ischaemia–reperfusion Injury in Prepubertal Rats

Abstract: 1. Rosiglitazone plays a positive role in the reparation of ischaemia-reperfusion (I/R) injury in different tissues. Thus, we examined its biochemical and histological effects on the contralateral testes to determine whether exogenous rosiglitazone affords any protection against testicular damage. 2. Forty-eight prepubertal male Wistar-Albino rats were divided into six groups. Testicular torsion was created by rotating the right testis 720 degrees in a clockwise direction for 5 h in all groups except group I, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Several theories have been postulated to explain this phenomenon, including auto‐immunization, subclinical episodes of contralateral testicular torsion, the release of acrosomal enzymes, paired neuroendocrine or vasomotor response during torsion, the presence of an underlying defect in spermatogenesis and the presence of inherent gonadal abnormality 13 . Recently, in agreement with the I/R injury hypothesis and the role of free radicals in the disease process, numerous experimental animal studies have confirmed the efficacy of anti‐oxidants, such as superoxide dismutase, catalase, allopurinol, rosiglitazone and aspirin, in reducing the short‐ and long‐term effects of spermatic cord torsion 5,12,15–19 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several theories have been postulated to explain this phenomenon, including auto‐immunization, subclinical episodes of contralateral testicular torsion, the release of acrosomal enzymes, paired neuroendocrine or vasomotor response during torsion, the presence of an underlying defect in spermatogenesis and the presence of inherent gonadal abnormality 13 . Recently, in agreement with the I/R injury hypothesis and the role of free radicals in the disease process, numerous experimental animal studies have confirmed the efficacy of anti‐oxidants, such as superoxide dismutase, catalase, allopurinol, rosiglitazone and aspirin, in reducing the short‐ and long‐term effects of spermatic cord torsion 5,12,15–19 …”
Section: Discussionmentioning
confidence: 93%
“…Testicular torsion is a widely studied experimental model. However, the pathogenesis of ipsilateral and contralateral testicular damage after unilateral testicular torsion remains poorly understood 9,13–15 . Several theories have been postulated to explain this phenomenon, including auto‐immunization, subclinical episodes of contralateral testicular torsion, the release of acrosomal enzymes, paired neuroendocrine or vasomotor response during torsion, the presence of an underlying defect in spermatogenesis and the presence of inherent gonadal abnormality 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Although PPAR-␤ and PPAR-␥ agonists have shown therapeutic effects against I/R injury (1,16), the effects of endogenous PPAR-␣ on conditions associated with I/R injury have not been investigated to date. A recent study of NRK-52E cells examined gentamicin-induced apoptosis, in which PGI 2 production was increased by infecting cells with an adenovirus carrying COX-1 and prostacyclin synthase (15).…”
Section: Discussionmentioning
confidence: 99%
“…Rosiglitazone is the most potent and selective peroxisome proliferator-activated receptor-gamma (PPAR-g) ligand. PPAR-g is a member of the nuclear hormone receptor superfamily involved in a number of physiological processes, including atherosclerosis, inflammation, cancer, infertility and demyelination (110). It has been demonstrated that rosiglitazone prevents cell injury by increasing endothelial NOS expression in the contralateral testicular tissue in a model of tIR (110).…”
Section: Other Mechanismsmentioning
confidence: 99%